Prognostic role of platelet lymphocyte ratio in advanced epithelial ovarian cancer - Amin, Rogina; Afrose, Taslima; Elora, Ashfi Laila; Chowdhury, Mina; Jolly, Rabeya Sultana; Kader, Mousumi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The platelet lymphocyte ratio (PLR) is an important prognostic biomarker in various cancers. Study was undertaken to determine the association between PLR and prognosis of advanced epithelial ovarian cancer. Methods: The prospective observational study was carried out gynecological oncology unit, department of gynecology and obstetrics Dhaka Medical College Hospital. Dhaka. Total 50 cases of diagnosed advanced epithelial ovarian cancer where enrolled during period from January 2021 to December 2021. Results: The mean age of participants was 52.8±11.5 years, with 68.0% being postmenopausal and 94.0% multigravida. Tumor grade III was most prevalent (58.0%), and the majority (62.0%) had serous carcinoma. Pre-operative CA-125 levels were <1000 in 72.0% of patients. The platelet-lymphocyte ratio (PLR) was <200 in 58.0% of patients, with no significant association between PLR and chemotherapy response (p=0.121). Progression-free survival was observed in 30.0%, with an overall survival of 58.0%. A significant association was found between PLR and survival outcomes (p=0.013). ROC analysis indicated an area under the curve of 0.726, establishing a cutoff value of ≥171.5 ng/ml for PLR, with 86.2% sensitivity and 66.7% specificity for predicting overall survival. Conclusions: This study suggested that the significant association was found between PLR with survival outcome. No significant association between PLR with before and after operation and chemotherapy.